Assembling a Co-produced urban lab: The case of Nuns' island, Galway. (September 2022) - Strohmayer, Ulf; Collins, Patrick; Rainey, Mark
Abstract: This paper details the contextual and conceptual elements involved in setting up an Urban Lab in the city of Galway, Ireland. The paper specifies the set-up of a lab in the post-industrial area of Nuns' Island, through a detailed reading of pertinent 'lab-centred' literatures. It contributes to this literature by (1) analysing a lab in the explicit context of an urban regeneration project and (2) exploring ways in which co-production may be put into practice. Urban Lab Galway is anticipated initially to play a major role supporting the urban regeneration of an area adjacent to a major university, which also owns substantial buildings and land on the site, and is thus not surprisingly supported by the local university in question. The paper motivates and details the reasons supporting co-produced initiatives, critically exploring the potential and difficulties attaching to such practices. The paper ends in a sustained engagement with the concept of 'creative destruction' in the context of lab-based engagements.